“Niveles de rentabilidad en los procesos de comercializaciòn y exportaciòn de cacao en la empresa boncao s.a. propuesta de reingeniería. año 2020” - Arroyo Zambrano, Gabriela Fernanda (2021)
Administrative management has a systemic nature, being the carrier of actions consistently oriented to the achievement of the objectives through the fulfillment of the classic functions of management in the administrative process: plan, organize, direct and control. The purpose of this study was to evaluate the profitability in the marketing and export of cocoa in Boncao S.A. located in the 4-sleeve enclosure via Buena Fe, Los Ríos Province, whose main mission is to market cocoa locally and export to the countries of Malaysia and Indonesia, for which simple random probabilistic sampling was applied; The research focused on two phases, in the first, a survey was carried out on administrative and financial staff to determine the profitability of the company and the second through a census, where information was collected from the organizational and financial structure of The company Boncao S.A. The economic analysis made it possible to determine that it is more beneficial to market the product rather than export, by marketing cocoa nationally it can do so in small batches which delivers and receives payment immediately effectively, as far as exporting that it has to invest all the capital that the company has, accumulate it until it completes the lot and the time of shipment arrives , the payment process takes 8 business days to become effective, so the company does not have financial liquidity to export but has enough liquidity to market within the province and the country. It was also found that the company does not have a marketing plan which is very important to achieve the desired goals of the company and achieve the strategic objectives, so it is suggested to implement one to have a better address of it. Keywords: cost effectiveness, commercialization, export, cocoa, marketing plan.